Copy number variations exploration of multiple genes in Graves' disease. Issue 4 (January 2017) - Song, Rong-hua; Shao, Xiao-qing; Li, Ling; Wang, Wen; Zhang, Jin-an
Abstract: Background: Few previous published papers reported copy number variations of genes could affect the predisposition of Graves' disease (GD). Herein, the aim of this study was to explore the association between copy number variations (CNV) profile and GD. Methods: The preliminary copy number microarray used to screen copy number variant genes was performed in 6 GD patients. Five CNV candidate genes (CFH, CFHR1, KIAA0125, UGT2B15, and UGT2B17) were then validated in an independent set of samples (50 GD patients and 50 matched healthy ones) by the Accucopy assay method. The CNV of the other 2 genes TRY6 and CCL3L1 was investigated in 144 GD patients and 144 healthy volunteers by the definitive genotyping technique using the Taqman quantitative polymerase-chain-reaction (Taqman qPCR). TRY6 gene-associated single nucleotide polymorphism (SNP), rs13230029, was genotyped by the PCR-ligase detection reaction (LDR) in 675 GD patients and 898 healthy controls. Results: There were no correlation of the gene copy number (GCN) of CFH, CFHR1, KIAA0125, UGT2B15, and UGT2B17 with GD. In comparison with that of controls, the GCN distribution of TRY6 and CCL3L1 in GD patients did not show significantly differ ( P > 0.05). Furthermore, TRY6-related polymorphism (rs13230029) showed no difference between GD patients and controls. No correlation was found between CNV or SNP genotype and clinical phenotypes. Generally, there were no link of the copy numbers of several genes, including CFH, CFHR1, KIAA0125, UGT2B15, UGT2B17, TRY6, and CCL3L1 to GD. Conclusion: Our results clearly indicated that the copy number variations of multiple genes, namely CFH, CFHR1, KIAA0125, UGT2B15, UGT2B17, TRY6, and CCL3L1, were not associated with the development of GD.